Government Finance Statistics Yearbook, 2014. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2015)
The IMF Government Finance Statistics contains statistical data on government financial operations for 156 countries. Where reported, the database contains time series from 1972 onwards using the Government Finance Statistics Manual 2014 (GFSM 2014) framework. The statistics, issued quarterly, are updated as new data are received and time series become available. These time series present combined statistics on revenue, expense, transactions in non-financial assets, and financial assets and liabilities, as well as on stocks of assets and liabilities of general government and its subsectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet